Pengaruh Servicescape Terhadap Kepuasan Pelanggan Bistro Restaurant Swiss-Bell Inn Hotel Bogo - Suryono, Joji; Rachman, Arief Faizal; Sembiring, Vienna Artina (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan DigitalDO - 10.30647/jpbd.v2i2.2090, 2026)
The objective of this research is to examine the impact of the servicescape on customer satisfaction at the Bistro Restaurant, Swiss-Bel Inn Hotel Bogor. The term "servicescape" encompasses the tangible aspects of the service environment, including spatial layout, hygiene, comfort, lighting, acoustics, and overall visual appeal, all of which contribute to customer perceptions. Customer satisfaction is conceptualized as an evaluative judgment resulting from the entire service encounter. This study adopts a quantitative methodology, utilizing a survey approach in which data were gathered through questionnaires administered to individuals who had dined at the restaurant. The data were analyzed using a simple linear regression technique to assess the degree of influence exerted by the servicescape on customer satisfaction. The findings reveal a statistically significant and positive relationship between servicescape quality and customer satisfaction. These results underscore the strategic role of physical environmental management in enhancing dining experiences and fostering customer loyalty. Keywords : Servicescape, Customer Satisfaction, Restaurant, Hotel, Physical   Environment